Antonio Gramsci : écrits politiques 2 : 1921-1922 - Gramsci, Antonio; Paris, Robert ([Paris] : Gallimard, 1975)
Bibliotheek François Vercammen
Frans
Meerdelige publicatie
Keywords: Partito Comunista Italiano (PCI).; communisme; Italië